Metal carboxylate complexes relevant to the Fischer-Tropsch synthesis - Pienaar, Andrew (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2005.